Analysis of the Combined Effects of Hydrodistillation and Ultrasound Methods on the Yield and Quality of Eucalyptus Leaf Oil - Novi Mailidarni; Jauhari Jauhari (Journal of Nutrition Science, 2024)
This study investigates the effects of combining hydrodistillation and ultrasound methods on the yield and quality of eucalyptus leaf oil. The study uses factorial randomized block design (RBD) with two replicates, focusing on the treatment variables of ultrasound exposure time and hydrodistillation temperature and pressure. The ultrasound exposure time is divided into three categories: 5-10 minutes, 15-20 minutes, and 25-30 minutes, while the hydrodistillation temperatures are set at 50-60 °C, 70-80 °C, and 90-100 °C. The essential oil yield and quality were analyzed using ANOVA and Least Significant Difference (LSD) tests. Results indicate that the combination of hydrodistillation at 70-80 °C with ultrasound exposure for 15-20 minutes significantly increases oil yield and enhances the chemical composition of eucalyptus oil, particularly its cineole content. This method shows potential as an alternative to traditional extraction techniques, offering improvements in both efficiency and product quality. keywords:  Cineole, Eucalyptus oil, Extraction yield, Hydrodistillation, Ultrasound